The Food Groups of MyPlate - Glenda L. Warren; Jennifer Walsh (EDIS)
Plan your food group choices wisely. Choose nutrient-rich foods that are fat-free or low-fat and low in added sugars. This 3-page fact sheet gives an overview of the MyPlate food groups. Written by Glenda L. Warren and Jennifer Walsh, and published by the UF Department of Family, Youth and Community Sciences, November 2012.